Enhancing the supercapacitor performance of NiCo2O4 microflowers by reduced graphene oxide nano-sheets - Worawee Saei; Prathan Buranasiri; Attaphol Karaphun; Chesta Ruttanapun; Chaval Sriwong (My University, 2021)
Abstract This work presented the preparation and supercapacitor performance of a spinel nickel-cobalt oxide (NiCo 2 O 4 ) microflowers mixed with nano-sized reduced graphene oxide (rGO) sheets. The hybrid material (NiCo 2 O 4 /rGO), pure NiCo 2 O 4 and nano-sized rGO samples were characterized and confirmed by several techniques, such as XRD, SEM and EDS. The supercapacitive properties of all prepared samples were also studied using an electrochemical measurement technique (CV and GCD). The results revealed that the NiCo 2 O 4 /rGO (484.1 F.g −1 ) hybrid electrode exhibited much higher specific capacitance than those of pristine NiCo 2 O 4 (358.3 F.g −1 ) and nano-sized rGO (113.8 F.g −1 ) electrodes, respectively. Hence, this work indicates that the supercapacitor performance of NiCo 2 O 4 mixed rGO hybrid materials is more superior to the pure NiCo 2 O 4 microflowers and nano-sized rGO sheets.
Keywords: Cobalt oxide; Supercapacitor Materials and Fabrication